同時多視点的手術記録システムの開発 - 鈴木, 直樹; 安田, 淳吾; 藤岡, 秀一; 岡本, 友好; 鈴木, 文武; 矢永, 勝彦; 船水, 尚武; 服部, 麻木 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Reduction in the number of surgeons is becoming a problem. It calls for urgent attention to build an effective education system as large amounts of knowledge, skill and experience is needed to train surgeons. This time, we have developed an imaging system that integrates synchronously taken images from various angles, not only from the existing surgical camera but also from fixed camera and wearable cameras on both the surgeon and the assistant. We could analyze and evaluate surgical technique by the imaging system. This surgical recording system which can obtain more information compared to existing single viewpoint image is likely to contribute to enhancing not only the techniques of surgeons but also staff at the surgical floor.